Insanity and criminal justice in Italy at the end of the 19th century - Vinci, Stefano (GLOSSAE. European Journal of Legal History, 2023)
The Italian penal code of 1889 introduced the concept of “mental infirmity” to circumscribe the hypotheses of non-punishability linked to the lack of consciousness or freedom of one’s acts at the time the criminal action was committed. The practical application of this rule required energetic intervention by the jurisprudence of legitimacy to circumscribe the exemption from punishment to the mere existence of pathological states and exclude it from passionate states.